2014
DOI: 10.1523/jneurosci.0017-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasticity at Different Sites across the Time Course of Cerebellar Motor Learning

Abstract: Learning comprises multiple components that probably involve cellular and synaptic plasticity at multiple sites. Different neural sites may play their largest roles at different times during behavioral learning. We have used motor learning in smooth pursuit eye movements of monkeys to determine how and when different components of learning occur in a known cerebellar circuit. The earliest learning occurs when one climbing-fiber response to a learning instruction causes simple-spike firing rate of Purkinje cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 59 publications
(25 reference statements)
5
69
0
1
Order By: Relevance
“…These data suggest that motor timing itself also strengthens the learning process in this paradigm, because the complex spikes associated with the conditioned response emerge and develop during the training and are phase locked to the initiation of the conditioned response, consolidating the learning process [204, 214]. Future studies will have to reveal to what extent the differences in simple spike modulations during these two forms of climbing fiber dependent motor learning mainly reflect the zebrin-positive and zebrin-negative character of the modules involved, whether they are due to the inherently different temporal character of the tonically driven VOR adaptation and the phasically driven eyeblink conditioning trials (see also [42, 218] for suppression mechanisms in trial by trial learning in zebrin-positive zones), and/or whether they are related to the direction of movements involved [27, 214, 215]. …”
Section: Cerebellar Learning and Timing Hypothesis Go Hand In Handmentioning
confidence: 99%
“…These data suggest that motor timing itself also strengthens the learning process in this paradigm, because the complex spikes associated with the conditioned response emerge and develop during the training and are phase locked to the initiation of the conditioned response, consolidating the learning process [204, 214]. Future studies will have to reveal to what extent the differences in simple spike modulations during these two forms of climbing fiber dependent motor learning mainly reflect the zebrin-positive and zebrin-negative character of the modules involved, whether they are due to the inherently different temporal character of the tonically driven VOR adaptation and the phasically driven eyeblink conditioning trials (see also [42, 218] for suppression mechanisms in trial by trial learning in zebrin-positive zones), and/or whether they are related to the direction of movements involved [27, 214, 215]. …”
Section: Cerebellar Learning and Timing Hypothesis Go Hand In Handmentioning
confidence: 99%
“…Animal work has shown that this form of adaptive learning is mediated, in part, by long-term depression of parallel fiber-Purkinje cell synapse in cerebellar cortex3031. In humans, studies using transcranial magnetic stimulation (TMS) to assess the inhibitory tone the CB exerts over M1 (cerebellar inhibition, CBI) have described changes in cerebellar excitability during motor adaptation studies89.…”
mentioning
confidence: 99%
“…This creates a mismatch between the predicted and actual sensory outcome of a movement, which drives error reduction in healthy individuals (Tseng et al, 2007;Shadmehr et al, 2010). The cerebellum is thought to be critical for learning error-based adaptation tasks (Martin et al, 1996;Diedrichsen et al, 2005;Chen et al, 2006) because patients with cerebellar degeneration show a marked impairment in such learning (Weiner et al, 1983;Martin et al, 1996;Smith and Shadmehr, 2005). In addition, acquisition of a visuomotor adaptation is enhanced when anodal transcranial direct current stimulation, a form of noninvasive excitatory stimulation, is applied over the cerebellum during training (Galea et al, 2011;Block and Celnik, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because this type of learning can transfer to untrained limbs (Sainburg and Wang, 2002;Criscimagna-Hemminger et al, 2003;Wang and Sainburg, 2004;Morton and Bastian, 2006;Savin and Morton, 2008;Balitsky Thompson and Henriques, 2010;Joiner et al, 2013), modulation of CBI in an untrained limb could be related to interlimb transfer (i.e., reflecting a somatotopy-specific plastic mechanism) or it could be a nonspecific response. Therefore, we also investigated CBI in the context of movement preparation in the absence of motor learning.…”
Section: Introductionmentioning
confidence: 99%